Tumor necrosis factor TNF-a alpha (Latakia University Journal -Medical Sciences Series, 2024)
Tumor necrosis factor alpha and nesting failure with its effects on gestational development, based on the fact that the ideal pregnancy in its various stages requires the development of an ideal utero-placental unit, and based on the fact that the placental unit needs the formation of the coronary villi responsible for maternal embryo transfer, which are formed from the villous gasoblasts and also need to form In the spiral arteries, which originate in extravillous invaginations, the effect of tumor necrosis factor, depending on the stage at which it affects what was previously mentioned, can lead to failure of nesting if it inhibits the transformation of invadoblasts into villous invaginations, or lead to chemical nesting if it inhibits the transformation of invaginations into Extravillous gasoblast However, if its effect is in the later stages, it may lead to miscarriage or continuation of the pregnancy with high arterial pressure or decreased fetal growth inside the uterus. The main mechanism of action of TNF alpha is to stabilize the expression of aquaporins 3 and 9, which are water channels responsible for the process of maternal-fetal blood exchange or the process of Inflammation mediated by cytokines and interleukins leads to the same result, and therefore it is accused of different roles, as for the mechanism of blood ischemia through inhibiting the migration of blood cells. Extravillous invasion and its penetration into the uterine myometrium, and this is consistent with the vascular role or an immune role mediated by cytokines and interleukins, resulting from the imbalance between immune rejection and immune tolerance, or the loss of the process of balance and coordinated action between fetal and maternal tissues by breaking the balance between the inflammatory state and immune-releasing factors.